2013
DOI: 10.1364/oe.21.025091
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous picosecond pulse generation in a diode-pumped Nd:YAP laser

Abstract: We present the first observation, to the best of our knowledge, the spontaneous generation of picoseconds pulse trains in a diode-pumped Nd:YAP laser with gigahertz repetition rate. Spatially dependent temporal dynamics were experimentally observed. After theoretically reconstruct the experimental temporal-resolved patterns, we verify that the complicated spatially-dependent temporal dynamics were originated from simultaneous coherent locking combination of fundamental and several additional higher-order trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Detailed investigation by [8] revealed that the transverse modes in degenerate cavity are phase-locked with each other, leading to field addition of the modes rather than intensity addition (the latter observed in multitransverse mode lasers). The field addition may be responsible for the observed spot size, that is smaller than the TEM 00 spot expected for the cavity, and the arbitrary mode patterns [9,10] and pulse behavior [11,12] observed in such cavities. In a separate experiment, it was observed that this sudden collapse of the cavity mode is also accompanied by a corresponding increase in the M 2 parameter, and a dip in the output power [13].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Detailed investigation by [8] revealed that the transverse modes in degenerate cavity are phase-locked with each other, leading to field addition of the modes rather than intensity addition (the latter observed in multitransverse mode lasers). The field addition may be responsible for the observed spot size, that is smaller than the TEM 00 spot expected for the cavity, and the arbitrary mode patterns [9,10] and pulse behavior [11,12] observed in such cavities. In a separate experiment, it was observed that this sudden collapse of the cavity mode is also accompanied by a corresponding increase in the M 2 parameter, and a dip in the output power [13].…”
Section: Introductionmentioning
confidence: 92%
“…It is well-established that the lowest possible spot size, in a real stable resonator, is governed by the value of the TEM 00 spot allowed for the cavity, and the value of TEM 00 spot does not depend on the size of the pump spot [5]. However, when the resonator is driven exactly to the point of g1g2 1∕2, keeping the pump spot size less than the TEM 00 mode spot size at the gain medium, the cavity suddenly transforms to a cavity with new features, due to the onset of TMD [6][7][8][9][10][11][12][13]. The most exciting feature of the cavity is that the mode size can be even lower than the value decided by the TEM 00 mode size, and it is primarily governed by the size of the pump spot.…”
Section: Introductionmentioning
confidence: 99%
“…The self-pulsing output can be realized by self-Q-switching and self-mode-locking techniques [19][20][21]. At present, the self-pulsing solid-state lasers in the 1 µm waveband have been widely investigated [22][23][24][25][26][27][28][29][30][31][32][33]. However, only a few self-pulsing solid-state lasers in the 2 µm spectral region have been reported [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…YAP crystal has a large nonlinear refractive index (n 2 = 7.3 × 10 −16 cm 2 W −1 ), which increases the self-phase modulation effect, and makes it be a promising candidate in SML operation [30]. Using Nd:YAP crystal as the gain medium, the SML operation at 1079.6 nm was successfully realized [31]. The maximum average output power was 550 mW at the incident pump power of 5 W, and the corre sponding optical conversion efficiency was 11%.…”
Section: Introductionmentioning
confidence: 99%